Efficacy of a Combined Treatment of Botulinum Toxin and Intensive Physiotherapy in Hereditary Spastic Paraplegia - Paparella, Gabriella; Vavla, Marinela; Bernardi, Lisa; Girardi, Giulia; Stefan, Cristina; Martinuzzi, Andrea (Frontiers in Neuroscience, 2020)
INTRODUCTION: The Hereditary Spastic Paraplegia (HSP) is a heterogeneous group of neurodegenerative disorders characterized by progressive spasticity and lower limbs (LL) weakness. There is no treatment to cure or halt the disease, except for symptomatic therapy. The use of botulinum toxin type A (BoNT-A) is one of the primary treatment for focal spasticity. Physiotherapy (PT) can help in maintaining residual functioning. We performed a retrospective study to evaluate effects of the combined BoNT-A and intensive PT in patients with HSP. METHODS: Eighteen adult patients (50% females) with clinical diagnosis of HSP were recruited. Eleven patients had a genetic diagnosis of SPG4, 5, 7, 8, 11, 72. Patients were all autonomously deambulant or needed support. BoNT-A was injected in 36 LL in different spastic muscles under electromyographic guidance and followed by intensive PT sessions. Outcome measures included disease severity, motor functional measures, perceived pain self-report and quality of life. Assessments occurred at baseline, 1 and 3 months after BoNT-A injection. RESULTS: Most inoculated muscles were hamstrings, rectus femoris and gastrocnemius which resulted in muscle tone improvement. We observed an improvement in the gait velocity and distance length. Spastic Paraplegia Rating Scale (SPRS) was significantly reduced after treatment, in addition to improving pain and quality of life. These results were riconfirmed in 3 months time. CONCLUSION: Our study indicates that combined treatment of BoNT-A and PT can lead to improvement of spasticity and quality of life in patients with HSP.